Use of Self-Assessment Questionaries with Moodle Surveys to Improve Reading Comprehension and Study Habits in Preservice Teacher Education - Ortega-Ruipérez, Beatriz (International Journal of Emerging Technologies in Learning (iJET), 2022)
Self-regulation strategies of learning are key to improving the learning process, and to teach students to use them, teachers must master them. To improve self-regulation of pre-service teachers, continuous self-assessments of their learning is included with Moodle survey resource. To measure the improvement of self-regulation, a pre-post study was conducted with two scales: ARATEX-R, for texts, and the inventory of self-regulation strategies, SRSI-SR, for study habits. Results showed a significant impact on self-regulation, specifically on planning, connecting ideas, subsequent assessment of difficulties and prior self-motivation. Continuous self-assessment has been key to improving reflection on the achievement of objectives on a weekly basis, and thus monitoring and improving learning planning throughout the course. This means that the Moodle survey resource can be very useful for self-assessment of learning in preservice teacher education, as well as being an easy to implement resource.